Rough set-inspired isolation forest - Rachwał, Albert; Karczmarek, Paweł; Rachwał, Alicja (Information sciences, 2025)
This paper presents an innovative approach to anomaly detection, combining the Isolation Forest method with Zdzisław Pawlak's rough set theory. The core methodology involves modifying the structure of binary trees used in Isolation Forests, allowing nodes to have more than the usual two children. Based on rough set theory, two approaches are developed: one where each node has three children, and another with five children per node. According to Pawlak's theory, lower and upper approximations are sought using the mean and standard deviation to define rough sets. This methodology is further enhanced by introducing a boundary region in the partitioned dataset, creating two variants: one with boundaries spanning from 1.5 to 3 standard deviations and another from 3 to 6 standard deviations. Each attribute is divided into a rough set comprising five subsets, with observations assigned to specific areas based on the defined limits, receiving corresponding weights. The proposed models are evaluated against the base Isolation Forest and K-Means-Based Isolation Forest, demonstrating notable improvements in performance. •Tree nodes are enhanced with rough set-based approximations.•Isolation Forest and its modifications are compared for efficiency.•Modifications significantly improve anomaly detection scores.